Building the Enemy: The Anti-Spaniard Movement in River Plate Revolutionary Literature (1810-1820) - Pérez, Mariana Alicia (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2010)
The revolutionary process initiated in 1810 was accompanied by political propaganda aiming at generating adherence and politically indoctrinate the River Plate population, which was mainly based on an anti-Spanish speech with the aim of defining the political enemy of the revolution: the Spaniards. This paper examines how Spaniards were represented in "patriotic" theater plays and poems written by revolutionary writers in the 1810's and how the anti-Spaniard movement developed in these works was understood and incorporated into the anti-Spanish imaginarium present in the River Plate society since colonial times.